Nurses' perspectives of recognising and responding to unsafe practice by their peers: A national cross‐sectional survey. Issue 7 (9th February 2021) - Blair, Wendy; Kable, Ashley; Palazzi, Kerrin; Courtney‐Pratt, Helen; Doran, Evan; Oldmeadow, Christopher
Abstract: Aims: This study aimed to identify behaviours and cues that nurses recognise as indications of unsafe practice, perceived factors that contribute to unsafe practice and actions nurses take in response. Design: Cross‐sectional survey. Methods: National cross‐sectional survey of a random sample of registered nurses (n = 231) in New Zealand, in 2017–2018. The STROBE Checklist was used to report this study. Results: Nurses reported a high rate of episodes of unsafe practices and recognised a range of behaviours and cues that alerted them to the potential for unsafe practice. Several organisational issues were perceived to contribute to unsafe practice occurring. The reporting of episodes of unsafe practice and perceived organisational support was low for nurses compared with managers. Conclusion: Failure to recognise and respond to unsafe practice may indicate a tolerance for substandard practice by individual nurses, or by the organisation. Nurses who recognise unsafe practice must be supported by the organisation.